Electrochemical profiling of natural furanocoumarins: DNA interaction dynamics of oxypeucedanin and prantschimgin - Hüseyin Oğuzhan Kaya; Gokay Albayrak; Hasan Isbilir; Fatma Kurul; Sura Baykan; Yeni Wahyuni Hartati; Seda Nur Topkaya (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: In this study, we present an electrochemical sensor for the detection of oxypeucedanin (Oxyp) and prantschimgin (Pra), two natural furanocoumarin derivatives. The determination of the effects of these molecules on DNA is important to be potential drug candidates. Our research focused on exploring the electrochemical behaviour of these compounds and their interaction with DNA. Experimental approach: The electrochemical properties of Oxyp and Pra were systematically analyzed by evaluating their oxidation currents. Changes in the oxidation currents and peak potentials of guanine bases were monitored before and after interaction in the solution phase and at the electrode surface. Key results: The limit of detection (LOD) and limit of quantitation (LOQ) for Oxyp were determined to be 1.3 and 4.3 µg/mL, respectively. For Pra, the LOD and LOQ were found to be 20 and 68 µg/mL, respectively. Stability studies demonstrated that the Oxyp solution retained its oxidation capacity for over a month, whereas the Pra solution retained its oxidation capacity for nearly 120 min. Our findings suggest that Oxyp interacts with dsDNA, potentially through electrostatic interactions, showing promise as a potential drug candidate targeting DNA. On the other hand, the interaction of Pra with dsDNA requires further exploration to fully understand its mode of action. Conclusion: The electrochemical sensor developed in this study provides a reliable and efficient method for detecting and analysing the interaction of these natural compounds with dsDNA. Our research contributes to advancing the understanding of the interaction between natural furanocoumarins and dsDNA, laying the groundwork for the design and development of novel and effective DNA-targeted drugs.